THE IMPORTANCE OF GOOD ENGLISH WRITING SYSTEM FOR THE BUSINESS PEOPLE IN PROMOTING THE PRODUCTS - jaenal, jaenal (TEXTURA, 2021)
The title of the research aims to know about The Importance of Good English Writing System for The Business People in Promoting the Products. Language of promotion has a power to persuade consumer’s desire to the product in society. It builds some images of ideology of product, then it also uses sign systems or language which has relationship with moral values of the customers. In this research, the writer used a descriptive method through literature study by collecting some data taken from relevant books or websites. The result of research shows that the business people should determine the right English writing when they want to promote the products. They should know not only the spelling, language purpose, but also the punctuations.Last but not least, the writer suggests the business people must notice and learn a lot on how to write good English sentences. It is a must for them to learn English grammar to make the understandable sentences for the customers.